Investigation of the Reaction between 3‐Benzisothiazolones, an Isoindole Isoster and Activated Acetylenes: Synthesis of Heterocyclic Backbones for Building Bioactive Molecules. (19th June 2014) - Incerti, Matteo; Vicini, Paola
<x xml:space="preserve">Abstract</x> Investigation of the reaction between benzo[d]isothiazol‐3‐one, 2‐aminobenzo[d]isothiazol‐3‐one, its isoster 2‐aminoisoindolin‐1‐one, and activated acetylenes, in the presence of triphenylphosphine, led us to synthesize novel heterocyclic compounds that could be attractive for the building of biologically active molecules. A one‐pot PPh3‐promoted tandem reaction, with acetylene dicarboxylates and dibenzoylacetylene, afforded new tricyclic pyrazolo‐fused benzisothiazoles. The PPh3‐promoted reaction between benzisothiazolones and methyl propiolate afforded 1, 4‐benzothiazepine‐5‐one derivatives, via an isothiazole ring expansion. These studies are providing additional insights in benzisothiazolone chemistry and describe simple and original synthetic accesses to novel derivatives.